1986
DOI: 10.1021/ac00297a022
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Km and Vmax for tryptic peptide hydrolysis using fast atom bombardment mass spectrometry

Abstract: 23) Katakuse, I.; Nakabushi, H.; Ichihara, T.; Sakurai, T.; Matsuo, T.; Matsuda, H. Int. J . Mass Spectrom. Ion Proc. 1984, 62, 17. (24) Morgan, T. G.; RabrenoviE, M.; Harris, F. M.; Beynon, J. H. Org. Mass (32) Castro, M. E.; Mallis, L. M.; Russell, D H. J Am. Chem. SOC. 1985, 107, 5652. (33) Mallis, L. M.; Russell, D. H., unpublished results. (34) Castro, M. E.; Mallis, L. M.; Russell, D. H., unpublished results. (35) Castro, M. E.; Russell, D. H. Fast atom bombardment mass spectrometry was used to provide q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
(1 reference statement)
3
9
0
Order By: Relevance
“…The resulting initial rates were comparable regardless of the method used, thus validating the mass spectrometry approach. Further studies using FAB‐MS to measure trypsin kinetics demonstrated K m and V max values for a number of peptide substrates that were consistent with literature values (Caprioli & Smith, 1986). These and numerous other early studies (review in Caprioli, 1987a,b), formed the groundwork for the use of mass spectrometry by biochemists and enzymologists to further understand their enzyme systems.…”
Section: Mass Spectrometry For Enzyme Assayssupporting
confidence: 86%
“…The resulting initial rates were comparable regardless of the method used, thus validating the mass spectrometry approach. Further studies using FAB‐MS to measure trypsin kinetics demonstrated K m and V max values for a number of peptide substrates that were consistent with literature values (Caprioli & Smith, 1986). These and numerous other early studies (review in Caprioli, 1987a,b), formed the groundwork for the use of mass spectrometry by biochemists and enzymologists to further understand their enzyme systems.…”
Section: Mass Spectrometry For Enzyme Assayssupporting
confidence: 86%
“…4C, V max /K m was directly proportional to the concentration of trypsin, and the slope of this linear plot afforded a value for the specicity constant (k cat /K m , k cat is the catalytic constant or turnover number), k cat /K m ¼ 6150 M À1 s À1 , which was in good agreement with values obtained using other assays. 21,[35][36][37] These results demonstrated that it was possible to monitor trypsin in real time and calculate enzyme kinetic parameters on the basis of the uorescence change of the QDs-cyt.c complex.…”
Section: Determination Of Trypsin-catalyzed Cytc Hydrolysis Kinetic P...mentioning
confidence: 99%
“…It is known that pepsin and trypsincatalysed hydrolysis, after different amino acid sequences, results in a wide range of kinetic parameters. 2,12,[44][45][46][47] It has been suggested that pepsin-catalysed hydrolysis of a peptide bond within a protein is more efficient than of short, synthetic peptides. 11 Our findings do not corroborate this.…”
Section: 32mentioning
confidence: 99%